Ag-rGO Nanocomposite as an Efficient Electrochemical Sensor for Thiourea. (4th August 2022) - Shafi, Murtaza; Bahader, Ali; Gul, Fazal Suhrab; khan, Alamgir; Habibullah,; Khan, M. Irshad; Farooqi, Kamran
Abstract : The nanofabrication of composites-based sensor can be routinely seen in the research literature, but high price restricts its use on a wider scale in the developing world for establishing sustainable society. Iraj Jodan Synthesized Ag-nanoparticles and alizarin yellow polymer based electrochemical sensor for thiourea detection. Alizarin yellow polymer provide stability, chemical attachment on the electrode surface but it is toxic to lungs, mucous membranes, and can cause organs damage by continuously disclosure to it. 1 For solving this problem, r-GO has pasted on electrode surface that provided excellent conduction as well as large surface area and had excellent sensitivity and low detection limit toward TU. Herein, this theme is materialized for the detection of thiourea (TU). Briefly, reduced graphene (r-GO) sheets with silver (Ag) nanoparticles impregnated were prepared via hydrothermal and chemical reduction method. The synthesized nano-composite material was characterized by various physiochemical techniques like FTIR, XRD, SEM and Cyclic Voltammetry (CV) and applied as synthesized for the detection and sensing of TU, a well-known carcinogen. The Ag-rGO changed electrode enhanced approximately three times greater anodic current as compared to rGO and five times greater anodic current as compare to GCE. Electrically and catalytically oxidation TU was achieved by GCE, GO, rGO and Ag-rGO at 0.2 V to 0.25 V applying cyclic voltammetry (CV). The concentrations were used 10 μ M to 50 μ M, while the current at anode increased as the concentration increased. The rGO and Ag-rGO also planned at various concentrations. The anodic current is increased by increasing scan rate of 20, 40, 60, 80 and 100 mV s −1 . So it could be used for recognition of TU in real time sample with good sensitivity, stability and reproducibility.